IMPLEMENTATION OF REAL TIME DATA AGGREGATION ON SMART METER WITH EDAS - Nirwana Mozef, Desti
Being a part of smart grid, smart meter is a device that is widely used nowadays because it is expected to improve the efficiency of the current electricity network by using advanced digital information and communication technology. One of the advantages of using smart meter is it can simplify the billing process. However, because the smart meter system must be connected to intranet and extranet networks, it becomes vulnerable to several security and privacy threats. Power consumption data from smart meter can reveal the homeowner’s personal information such as their lifestyle and economy status. Although some research has been carried out in this direction, but most of the existing solutions are computationally complex and not suitable for smart meter’s resource which is limited. In this research, we did an implementation of real time data aggregation on smart meter system using Efficient Data Aggregation Scheme (EDAS) which is more suitable for smart meter because it is used symmetric key cryptography primitive such as hash function which cause very limited computational overhead. The testing is done by implementing a system model consisting of Home Gateway (HG), Third Party Aggregator (TPA), and Service Provider (SP). After that, a secure data aggregation method is applied to the system using EDAS method which consists of 3 phases such as authentication, billing calculation, and energy management. The results of this study indicate that several security properties such as authentication, data confidentiality, data integrity, user privacy, and forward secrecy can be maintained. In addition, service providers can also calculate bills for each customer from data received from smart meters. Other qualitative and quantitative results are computational tests, security analysis on the system, and analysis of problems during the implementation process. Computational tests are conducted by calculating each function performed, for example hashing functions, encryption, decryption, etc. per component on the system to see its efficiency.